Oskar Kokoschka Kunst und Politik 1937-1950 - Werkner, Patrick (2003)
Result of our research is a monographic study dealing with a prominent part of Kokoschka's life and work which has hitherto been regarded too little by scholars. The years of his exile in Prague and particularly in London, where he had to work under a lot of stress and pressure, are the time in which his political allegories came to be. As these works are outside the established canon of art historical development, and as they have no affinity to Surrealism or to Abstract art, scholars have so far spent comparatively less effort to analyse them. This study approaches the group of these works from a transdisciplinary perspective. The authors (G. Sultano is trained historian, P. Werkner art historian) set out from different questions with regard to his oevre and his life. This results in combining the view of a prominent body of Kokoschka's paintings with a biographical perspective set against a political-historical background.